Plan de negocio para la creación de una empresa consultora en Customer Experience Management (CEM) en la ciudad de Quito, enfocada en los establecimientos de alojamiento de primera y segunda categoría - Montaño Bravo, Carla Camila (2019)
The thesis hereby is about the creation of a business plan of a consulting agency in the field of Customer Experience Management (CEM). The company will be located in the city of Quito and its name is Experience Consulting Group (ECG). The market that is going to be studied is mostly the accommodation establishment of first and second categories of the administrative areas of Eugenio Espejo and La Mariscal. The project has been contextualizing and providing background information about the general concept of consulting, the origin of CEM, the importance of CEM in the hotel industry and the perception of CEM in the hotel sector of Quito. In addition, a strategic plan has been developing in which the environment and competitiveness analysis of the ECG have been carried out, including a SWOT cross analysis chart. Through the establishments of the mission, vision, business objectives and an organizational structure. For market research and analysis, the descriptive methodology is applied through a survey focused on the qualitative and quantitative information collected. For this purpose, surveys were carried out on accommodation and interviews with experts on consultancy and CEM. Additionally, marketing strategies are formulated focused on the marketing mix of services. An appropriate operational plan is prepared for ECG focused on a methodology and aims to work by projects. On the other hand, the location of the office, the installed capacity, the flow of the steps of the consultancy phases and the service quality policy offered by ECG are presented. Through a financial evaluation, the feasibility of the business idea of the consulting company ECG is determined. In this analysis, different financial indexes and balances are shown in detail. The most important being the NVP (Net Present Value) and IRR (Internal Rate of Return) because they establish the feasibility and viability of the project.